Respuesta :

Answer:

  (x, y) = (-3, 2)

Step-by-step explanation:

For equations that involve tedious math, I like to let a graphing calculator do it. The solution is ...

  (x, y) = (-3, 2)

_____

Fully equivalent to solution by elimination is the use of Cramer's rule. It tells you ...

  Δ = (-9.3)(1.7) -(7.1)(8.6) = -76.87

  x = ((45.1)(1.7) -(-17.9)(8.6)) / Δ = 230.61/-76.87 = -3

  y = ((-9.3)(-17.9) -(7.1)(45.1)) / Δ = -153.74/-76.87 = 2

The solution is (x, y) = (-3, 2).

Ver imagen sqdancefan
ACCESS MORE